Antibodies to Seasonal Coronaviruses Rarely Cross-React With SARS-CoV-2: Findings From an African Birth Cohort. Issue 12 (17th September 2021) - Zar, Heather J.; Nicol, Mark P.; MacGinty, Rae; Workman, Lesley; Petersen, Wonita; Johnson, Marina; Goldblatt, David
Abstract : Supplemental Digital Content is available in the text. Abstract : Antibodies to seasonal human-coronaviruses (sHCoV) may cross-protect against SARS-CoV-2. We investigated antibody responses in biobanked serum obtained before the pandemic from infants with polymerase chain reaction-confirmed sHCoV. Among 141 samples with antibodies to sHCoV, 4 (2.8%) were positive for SARS-CoV-2-S1 and 8 (5.7%) for SARS-CoV-2-S2. Antibodies to sHCoV rarely cross-react with SARS-CoV-2 antigens and are unlikely to account for mild pediatric illness.